PERAN BIMBINGAN KELOMPOK DENGAN MEDIA ULAR TANGGA DALAM MENINGKATKAN LEARNING INTEREST SISWA KELAS IX C SMPN 2 SELOGIRI - Dwiana, Awista; Sri Suryanti, Hera Heru; Jawandi, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of group guidance services using snakes and ladders game media in improving the learning interest of class IX C students at SMP Negeri 2 Selogiri in the 2025/2026 academic year. The study was conducted at SMP Negeri 2 Selogiri and involved ten students who were categorized as having low learning interest. The research employed Guidance and Counseling Action Research (PTBK) implemented in three cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through learning interest questionnaires, observations, interviews, and documentation. The results showed a gradual improvement in students’ learning interest after the implementation of group guidance services using snakes and ladders game media. In the pre-cycle stage, students’ learning interest was 54% and categorized as low. It increased to 60% in Cycle I, 70% in Cycle II, and showed a significant improvement to 83% in Cycle III, with a total increase of 29% from the initial condition. This improvement indicates that learning interest indicators, including enjoyment, attention, interest, and student involvement, met the predetermined success criteria. Based on these findings, it can be concluded that group guidance services using snakes and ladders game media are effective in improving the learning interest of class IX C students at SMP Negeri 2 Selogiri.